A Cost-Effective System of Renewable Micro Grid using Glowworm Swarm Optimization Algorithm - Gnanaprakash, M.; Mangaiyarkarasi, S.P.; Tony, A. Cherish (Journal of Lumbini Engineering College, 2022)
Due to today's rapid socioeconomic expansion and environmental concerns, many modern civilizations are interested in researching alternate energy options, notably renewable ones. In this sense, a Micro-grid (MG) of multiple renewable energy sources can help achieve the intended goals while delivering electricity more efficiently, affordably, and safely. This paper presents an expert multi-objective Glowworm Swarm Optimization Algorithm (GSO) for optimal operation of a typical MG with Renewable Energy Sources (RESs). The objective is to minimize both the overall operating cost and the net emission. The proposed algorithm is tested on a typical MG, and its superior performance is compared to those from other evolutionary algorithms.